Update on the use of immunoglobulin in human disease: A review of evidence - Perez, Elena E.; Orange, Jordan S.; Bonilla, Francisco; Chinen, Javier; Chinn, Ivan K.; Dorsey, Morna; El-Gamal, Yehia; Harville, Terry O.; Hossny, Elham; Mazer, Bruce; Nelson, Robert; Secord, Elizabeth; et al. (Journal of allergy and clinical immunology, 2017)
Human immunoglobulin preparations for intravenous or subcutaneous administration are the cornerstone of treatment in patients with primary immunodeficiency diseases affecting the humoral immune system. Intravenous preparations have a number of important uses in the treatment of other diseases in humans as well, some for which acceptable treatment alternatives do not exist. We provide an update of the evidence-based guideline on immunoglobulin therapy, last published in 2006. Given the potential risks and inherent scarcity of human immunoglobulin, careful consideration of its indications and administration is warranted.